SAYYID QUTHB’S THOUGHT ON CHARACTERISTICS OF IDEAL LEADER IN AL QUR’AN: (A Study in Tafsîr fî Zhilal al-Qur'ân) - Fitriawan, Aidul; Ridho, Abdul Rasyid (UIN Mataram, 2023)
Every country or region desires to be led by a qualified person. However, not all countries or regions are able to get it. In addition to limited human resources, the debate about the criteria of the ideal leader is still unfinished. This research emphasizes more on subjective assessment, namely the characteristics of ideal leaders according to Sayyid Qutbh in Tafsîr fî Zhilâl al-Qur'ân. This research uses library research. The data collection method used is the documentation method, while the analysis method used is the maudh?'i method commonly known as thematic studies. The results of this study indicate that some of the characteristics of ideal leaders according to Sayyid Quth are honest, trustworthy, fair, professional, and like to deliberate.